Handbook of research on developing circular, digital, and green economies in Asia - Ordóñez de Pablos, Patricia 1975- (IGI Global, 2021)
"This book explores new and emerging business and management practices to support companies and economies in the digital transformation in Asia, with special emphasis on success and failure experiences and analyzing the role of digital skills and competences, green issues and technological disruptors in these emerging practices in Asia and how they can contribute to the creation of new business opportunities, more jobs and growth for the recovery of Asian economies after the pandemic"--
Includes bibliographical references and index
Chapter 1. Circular economy for plastics and digitally enabled community towards ASEAN Halal Hub in Asia -- Chapter 2. Digital leadership competencies in the Malaysian context: a study in manager levels -- Chapter 3. Impact of COVID-19 vaccines on tourism demand and culture -- Chapter 4. Quantitative analysis of strategic human resource management and organizational learning: the sustainability of MSMEs in Brunei Darussalam -- Chapter 5. Policies for promotion of Malaysian SMEs go global in the digital economy: SMEs go global from Malaysia -- Chapter 6. A study on the internet usage pattern of youths in Sikkim -- Chapter 7. Influence of industry 4.0 on Asia: motives and cultures in the post-COVID-19 era -- Chapter 8. Impact of supervisor feedback, customer-employee exchange, and creative personal identity on innovative behavior -- Chapter 9. Propensity to purchase organic food: an integrative model of consumption values in Malaysia --
- Chapter 10. Practicing circular economy in India: insights of business models on the three paradigms reduce, reuse, and recycle -- Chapter 11. Reconfiguration of the Indian film industry during the COVID-19 pandemic: the enablers and the impeders -- Chapter 12. New business development strategy of telecommunication operators based on a smart energy system: case of KT-MEG (enhanced) -- Chapter 13. An automated geometric appraisal model: a computerized performance-based incentive policy suitable for HEIs in India -- Chapter 14. Exploratory study on user satisfaction of e-HRM: evidence from Brunei government employee management system (GEMS) -- Chapter 15. Green consumerism in Brunei Darussalam: exploratory study on purchasing behaviour -- Chapter 16. Prospect of promoting Sikkim as a smart tourism destination: a descriptive analysis -- Chapter 17. An explanatory study of user satisfaction: evidence from Brunei health information and management system (bru-HIMS) --
- Chapter 18. Employee motivation for training and development: a study of a pharmaceutical company in Sikkim -- Chapter 19. Employee performance in the fast food industry: a mediating role of happiness -- Chapter 20. The influence of training, performance appraisal, and organizational support on employee service behavior with compensation as a mediator -- Chapter 21. Technology gap: information and communication technology trade and sustainability issues in India. - Mode of access: World Wide Web
Keywords: Managerial economics / fast; Sustainable development / Economic aspects / fast; Technological innovations / Economic aspects / fast; Managerial economics -- Asia; Technological innovations -- Economic aspects -- Asia; Sustainable development -- Economic aspects -- Asia; Asia / fast